2018
DOI: 10.23962/10539/26171
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Use by Zimbabwean Smallholder Farmers: A Baseline Study

Abstract: This article provides findings from a baseline study on mobile phone use by smallholder farmers in Zimbabwe. The study investigated use of mobile phones by 58 farming households in a village in Zimbabwe's Midlands Province. Via a survey questionnaire and a focus group discussion, the study found that 100% of the surveyed households identified "asymmetry of information" as a challenge they face in their agricultural activities, and 90% cited "absence of market information" as a challenge. Yet at the same time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…This was attested by Kassem et al (2020) found high level of farmers' (63.88%) utilization of mobile-based advisory services information, whereas, the moderate level accessed fewer (42%) information, on the other hand, low level accessed the fewest information (21%). In line to this, Musungwini (2018) found low levels of household mobile phone usage, with only 50% of households were found to be using mobile telephony in support of a farming activity. In the same note, Akinwale et al (2019) discovered the low utilization level of internet, WhatsApp, Facebook and emails…”
Section: Level Of Farmers' Utilization Of Mobile Phone Individual And...mentioning
confidence: 59%
“…This was attested by Kassem et al (2020) found high level of farmers' (63.88%) utilization of mobile-based advisory services information, whereas, the moderate level accessed fewer (42%) information, on the other hand, low level accessed the fewest information (21%). In line to this, Musungwini (2018) found low levels of household mobile phone usage, with only 50% of households were found to be using mobile telephony in support of a farming activity. In the same note, Akinwale et al (2019) discovered the low utilization level of internet, WhatsApp, Facebook and emails…”
Section: Level Of Farmers' Utilization Of Mobile Phone Individual And...mentioning
confidence: 59%
“…De esta forma, el acceso a la telefonía móvil ha coadyuvado, en el mundo rural, a reducir las asimetrías de información a partir de las transferencias de información de precios y mercado. La reducción de costos de transacción y conectividad al mercado, que concluye en una mejora de sus ingresos, contribuye a que los hogares rurales tengan la posibilidad de consumir bienes de clase media o, hasta ahora, de lujo como celulares, electrodomésticos y vehículos (Khan et al, 2019;Musungwini, 2018;Sekabira & Qaim, 2017). Ello, debido al desarrollo del acceso al financiamiento a través de fuentes formales e informales, propias de las dinámicas sociales del consumidor rural, que ha permitido el consumo financiado de dichos bienes como el de telefonía móvil (Ortiz, 2017).…”
Section: Discussionunclassified
“…Moreover, Mariyono's [24] fndings shows that education, experience, and distance to market in vegetable is negative and afects the participation of intensive commercial vegetable farming and marketing, while credit availability has a positive efect. Access to available information and its devices [25][26][27][28] reduces transaction cost and increase customers as well as production and productivity. Mohammed Kassaw et al [29] also identifed as education, distance to market, credit were identifed as the main determinants of the choice of market outlet choices for vegetables.…”
Section: Literature Review On Of Determinants Of Market Outlet Choice...mentioning
confidence: 99%